HYDROGEN PRODUCTION USING Rhodobium Marinum IN MILK LIQUID WASTE - Anam, Khairul; Susilaningsih, Dwi (LIPI Press, 2015)
This study was conducted to investigate the effect of dilution towards milk liquid waste in biologically producing hydrogen gas by photosynthetic bacteria, Rhodobium marinum. The methods included pretreatments of the milk liquid waste by sterilization, filtration, neutralization, and centrifugation, before and after dilution. From several experiments, 100% of milk liquid waste substrate generated the highest hydrogen gas production up to 93.45 16.15 ml, but the highest efficiency was obtained at level 12.5% of milk liquid waste substrate which valued 0.33 mol hydrogen/ mol glucose consumed. Kinetics measurements for hydrogen production process in milk liquid waste which was added with nutrients obtained yield of biomass formed per substrate consumed (Yx/s) i.e. 0.192 g/g, yield of product per substrate (Yp/s) i.e. 0.009 g/g, and yield of product produced per biomass (Yp/x) i.e. 0.043 g/g. For kinetics measurements on the milk liquid waste medium without nutrients addition, obtained Yx/s was 0.261 g / g, Yp/s was 0.019 g/g and Yp/x was 0.070 g/g